PENERAPAN MODEL PEMBEJARAN MIND MAPPING MELALUI BIMBINGAN KELOMPOK UNTUK MENINGKATKAN KREATIVITAS SISWA KELAS VIII-2 SMP MUHAMMADIYAH 02 MEDAN - Aulya Hasibuan, Suryati; Deliati, Deliati (BRIGHT VISION Journal of Language and Education, 2023)
The aim of this research is to determine the application of the mind mapping learning model through group guidance services through modeling techniques to increase the creativity of students at SMP Muhammadiyah 02 Medan for the 2022/2023 academic year. The objects of this research were 8 students of VIII-2 SMP Muhammadiyah 02 Medan who had low creativity. Service implementation is carried out in one group guidance service cycle. The research design in this study is planning, action, observation and reflection. To obtain data and information in this research, observations and interviews were carried out. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the data analysis that has been described, it can be understood that the application of the mind mapping learning model through guidance services implemented in class VIII-2 of SMP Muhammadiyah 02 Medan for the 2022/2023 academic year can increase student creativity.